2021
DOI: 10.1093/molbev/msab123
|View full text |Cite
|
Sign up to set email alerts
|

Conserved and unique transcriptional features of pharyngeal arches in the skate (Leucoraja erinacea) and evolution of the jaw

Abstract: The origin of the jaw is a long-standing problem in vertebrate evolutionary biology. Classical hypotheses of serial homology propose that the upper and lower jaw evolved through modifications of dorsal and ventral gill arch skeletal elements, respectively. If the jaw and gill arches are derived members of a primitive branchial series, we predict that they would share common developmental patterning mechanisms. Using candidate and RNAseq/differential gene expression analyses, we find broad conservation of dorso… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 132 publications
1
26
0
Order By: Relevance
“…The elephant shark JRS1 sequence drove reporter expression in the joint of the zebrafish first (mandibular) pharyngeal arch, consistent with other gnathostomes, but gene expression of nkx3.2 in the related elasmobranch chondrichthyans has been reported in the intermediate domains of all pharyngeal arches, including the hyoid and gill arches (Compagnucci et al, 2013;Hirschberger et al, 2021). If we assume elephant shark nkx3.2 gene expression mirrors that of elasmobranchs and that JRS1 drives nkx3.2 gene expression in all pharyngeal arches, our results would support the conclusion that much of the gene regulatory landscape of osteichthyan mandibular joints is found more broadly in the pharyngeal arches of chondrichthyans (Hirschberger et al, 2021). JRS1 knockout did not phenocopy the striking jaw joint fusion seen in zebrafish nkx3.2 gene knockout mutants (Miyashita et al, 2020;Waldmann et al, 2021), suggesting this enhancer is not essential for nkx3.2 expression at the time points analysed.…”
Section: Discussionsupporting
confidence: 67%
“…The elephant shark JRS1 sequence drove reporter expression in the joint of the zebrafish first (mandibular) pharyngeal arch, consistent with other gnathostomes, but gene expression of nkx3.2 in the related elasmobranch chondrichthyans has been reported in the intermediate domains of all pharyngeal arches, including the hyoid and gill arches (Compagnucci et al, 2013;Hirschberger et al, 2021). If we assume elephant shark nkx3.2 gene expression mirrors that of elasmobranchs and that JRS1 drives nkx3.2 gene expression in all pharyngeal arches, our results would support the conclusion that much of the gene regulatory landscape of osteichthyan mandibular joints is found more broadly in the pharyngeal arches of chondrichthyans (Hirschberger et al, 2021). JRS1 knockout did not phenocopy the striking jaw joint fusion seen in zebrafish nkx3.2 gene knockout mutants (Miyashita et al, 2020;Waldmann et al, 2021), suggesting this enhancer is not essential for nkx3.2 expression at the time points analysed.…”
Section: Discussionsupporting
confidence: 67%
“…Although the pseudobranch clearly appears to develop from the posterior side of the mandibular arch in the skate, we sought to directly confirm this embryonic origin by cell lineage tracing. We and others have previously reported that foxl2 is expressed in the core mesoderm and presumptive gill-forming epithelium of the pharyngeal arches of cartilaginous fishes (Wotton et al, 2007;Hirschberger et al, 2021). Analysis of foxl2 expression by mRNA in situ hybridisation (ISH) in skate embryos at S24 reveals these expression patterns not only in the developing hyoid and gill arches, but also in the developing mandibular arch (Fig.…”
Section: The Skate Pseudobranch Is Mandibular Arch-derivedmentioning
confidence: 91%
“…Chromogenic mRNA in situ hybridisation (ISH) for foxl2 (MW457610), gata2 (MZ501824), shh (EF100667) and ptc (EF100663) was performed in wholemount as in Hirschberger et al (2021), and on paraffin sections as in O'Neill et al (2007) with modifications according to Gillis et al (2012). mRNA ISH by chain reaction (HCR) on paraffin sections was carried out according to Choi et al (2018), with modifications as described in Criswell and Gillis (2020).…”
Section: Mrna In Situ Hybridisation and Immunofluorescence On Paraffin Sectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…So, both ancestral jawed vertebrates and stem chondrichthyans had endoskeletal bone. What about living chondrichthyans, which are thought to retain the most ancestral vertebrate features ( Criswell and Gillis, 2020 ; Hirschberger et al, 2021 )? Despite all of these phylogenetic data, the chondrichthyan endoskeleton has traditionally been characterized as lacking bone ( Ørvig, 1951 ; Zangerl, 1966 ; Moss, 1977 ; Janvier, 1981 ; Maisey, 1988 ; Clement, 1992 ).…”
Section: Chondrichthyan Subperichondral Bone-like Tissues Might Be Homologous To Perichondral Bonementioning
confidence: 99%